Promoting Learning for Bilingual Pupils 3?11 : Opening Doors to Success. - Conteh, J. (Sage Publications, 2006)
Written by a team of teachers, this clear and accessible book shows readers how they can help bilingual learners in their classrooms to access the curriculum as effectively as possible. Advice is included on: "developing whole-school policies. "creating positive classroom settings to promote learning. "using drama. "supporting bilingual learners in the early years. "the importance of home-school links. There are also plenty of practical suggestions for ways to improve classroom practice, and some photocopiable material.